2023
DOI: 10.1093/plcell/koad291
|View full text |Cite
|
Sign up to set email alerts
|

Expansin SlExp1 and endoglucanase SlCel2 synergistically promote fruit softening and cell wall disassembly in tomato

Guanqing Su,
Yifan Lin,
Chunfeng Wang
et al.

Abstract: Fruit softening, an irreversible process that occurs during fruit ripening, can lead to losses and waste during postharvest transportation and storage. Cell wall disassembly is the main factor leading to loss of fruit firmness, and several ripening-associated cell wall genes have been targeted for genetic modification, particularly pectin modifiers. However, individual knockdown of most cell wall–related genes has had minimal influence on cell wall integrity and fruit firmness, with the notable exception of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…Conversely, simultaneous overexpression of these genes promoted early fruit softening. These results support the conclusion that these two genes have a synergistic effect on fruit softening [ 141 ]. Furthermore, the bHLH transcription factor BRI1-EMS-SUPPRESSOR1 (BES1) encoded by Solyc04g079980 has been identified as an upstream regulator of fruit softening through the activation of cell-wall degradation during ripening [ 142 ].…”
Section: Gene Editing In Tomato Breedingsupporting
confidence: 89%
See 1 more Smart Citation
“…Conversely, simultaneous overexpression of these genes promoted early fruit softening. These results support the conclusion that these two genes have a synergistic effect on fruit softening [ 141 ]. Furthermore, the bHLH transcription factor BRI1-EMS-SUPPRESSOR1 (BES1) encoded by Solyc04g079980 has been identified as an upstream regulator of fruit softening through the activation of cell-wall degradation during ripening [ 142 ].…”
Section: Gene Editing In Tomato Breedingsupporting
confidence: 89%
“…However, only mutations in the PL gene Solyc03g111690 , resulted in firmer fruits [ 140 ]. Simultaneous knockout of two genes, one encoding a fruit ripening-associated α-expansin ( Solyc06g051800 ) and the other an endoglucanase ( Solyc09g010210 ), using CRISPR/Cas9 improved fruit firmness [ 141 ]. Conversely, simultaneous overexpression of these genes promoted early fruit softening.…”
Section: Gene Editing In Tomato Breedingmentioning
confidence: 99%
“…The expression of the four candidate EXPs dramatically increased when firmness decreased in strawberries [30]. In tomatoes, SlEXP1 promoted fruit softening cooperating with SlCel2 [18]. It is worth noting that ethylene responsive elements and abscisic acid responsive elements were detected in the promoter region of PpEXPA7, PpEXPA13 and PpEXPA15; therefore, we propose that PpEXPs might be involved in regulating fruit textures in peaches.…”
Section: Discussionmentioning
confidence: 76%
“…There is increasing evidence that softening is a complex process that involves multiple genes. PG, PME, PL, β-galactosidase arabinofuranosidase and expansin have been proven to be involved in the softening of tomatoes [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Various crucial hydrolases, such as polygalacturonase (PG), pectin methylesterase (PME), pectate lyase (PL), β-galactosidase (TBG), endotransglycosylase (XTH), and endo-glucanase (CEL), are responsible for cellular wall disassembly during fruit ripening [ 45 , 46 ]. In addition, Expansin (EXP) also plays a role in the regulation of fruit softening [ 47 ]. In this study, we observed that treatment with LCH led to the upregulation of cell wall degradation-related genes such as PG2a , PL , PL8 , TBG4 , and EXP1 , contributing to the delayed ripening of tomato fruit.…”
Section: Discussionmentioning
confidence: 99%